2018
DOI: 10.1126/scitranslmed.aag1328
|View full text |Cite
|
Sign up to set email alerts
|

Sensory deprivation after focal ischemia in mice accelerates brain remapping and improves functional recovery through Arc-dependent synaptic plasticity

Abstract: Recovery after stroke, a major cause of adult disability, is often unpredictable and incomplete. Behavioral recovery is associated with functional reorganization (remapping) in perilesional regions, suggesting that promoting this process might be an effective strategy to enhance recovery. However, the molecular mechanisms underlying remapping after brain injury and the consequences of its modulation are poorly understood. Focal sensory loss or deprivation has been shown to induce remapping in the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…Photothrombosis. Photothrombosis was performed as previously described (71). This protocol induces focal, well-circumscribed, and highly reproducible lesions (72).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photothrombosis. Photothrombosis was performed as previously described (71). This protocol induces focal, well-circumscribed, and highly reproducible lesions (72).…”
Section: Methodsmentioning
confidence: 99%
“…Individual data points represent individual mice. Sample size and specific time points were selected on the basis of previous studies examining network connectivity changes in mice (34,41,71). Prism 8 software was used to perform statistical testing.…”
Section: Methodsmentioning
confidence: 99%
“…In mice, macroscopic brain imaging studies have similarly shown a range of alterations in cortical activity maps after stroke (Brown et al, 2009;Harrison et al, 2013;Jablonka et al, 2010;Kraft et al, 2018;Mohajerani et al, 2011), but whether those were associated with functional recovery has not been established. In a landmark in vivo calcium imaging study often cited as the best evidence for remapping after stroke, some neurons in peri-infarct cortex were more broadly tuned after stroke compared to neurons in control mice without a stroke (Winship et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, longitudinal imaging studies in barrel cortex suggested that inactive neurons are recruited during spared whisker map plasticity 60 . Previous stroke studies from our lab and others have found that mesoscopic sensory and motor maps can shift or displace after stroke 36,[62][63][64] , which implies there might be re-mapping of function at a cellular level. Although Winship and Murphy (2008) convincingly showed that forelimb selective neurons could become responsive to another limb after stroke, it was unknown that if same neurons could become more or less responsive to the same limb over time.…”
Section: A Subset Of Vip Neurons Are Highly Sensitive To the Effects mentioning
confidence: 78%